1997
DOI: 10.1086/513665
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Reactions to Thalidomide in Patients Infected with Human Immunodeficiency Virus

Abstract: Thalidomide is emerging as a useful agent in the management of several complications of disease due to human immunodeficiency virus (HIV). We conducted three prospective studies of 56 HIV-infected patients who were treated with thalidomide for 14-21 days; 24 (43%) of these patients discontinued therapy owing to adverse reactions. Cutaneous and/or febrile reactions were the most frequent toxicities, arising in 20 (36%) of the patients. These reactions occurred after a mean interval (+/-SD) of 10 +/- 3 days and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 4 publications
1
31
0
3
Order By: Relevance
“…[25][26][27] Thalidomide use in subjects with AIDS who have aphthous ulcers 41 and wasting syndrome 10 has not been reported to result in TPN. In contrast, Wulff et al 27 suggested that with longterm treatment (1-6 years) in PN, all subjects develop signs of neuropathy.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…[25][26][27] Thalidomide use in subjects with AIDS who have aphthous ulcers 41 and wasting syndrome 10 has not been reported to result in TPN. In contrast, Wulff et al 27 suggested that with longterm treatment (1-6 years) in PN, all subjects develop signs of neuropathy.…”
Section: Commentmentioning
confidence: 99%
“…3,4 In HIVinfected subjects, thalidomide has been used to treat cachexia 10,11 and oral aphthous ulcers. 12 Thalidomide is associated with teratogenicity (phocomelia), [13][14][15] peripheral neuropathy, [16][17][18][19][20] and drug reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Los datos de algunas investigaciones sugieren que los infectados por el virus VIH sufren una mayor incidencia de efectos secundarios al seguir un tratamiento con talidomida que los VIH n e g a t i v o s 4 . Uno de los efectos descritos en los VIH positivos es la aparición de reacciones de hipersensibilidad caracterizadas por la presencia de rash y/o fieb r e 4 .…”
unclassified
“…Uno de los efectos descritos en los VIH positivos es la aparición de reacciones de hipersensibilidad caracterizadas por la presencia de rash y/o fieb r e 4 . Por tanto, hay evidencia de que la talidomida puede producir fiebre de forma aislada en pacientes VIH y reacciones de hipersensibilidad con fiebre y rash tanto en infectados por el virus como en seronegativos, pero son muy escasas las publicaciones médicas (búsqueda en la base de datos Micromedex y Medline desde enero de 1984 hasta 1999) en las que sean descritos casos de fiebre de forma aislada en pacientes VIH negativos 5,6 .…”
unclassified